A Comparative-Correlational Study of Emotional Intelligence and Musical Intelligence among Students from Years Eight to Eleven at Modern International School Bangkok, Thailand - Sachathep, Laxshmi; Lynch, Richard (Scholar: Human Sciences, 2016)
In this study, emotional intelligence and musical intelligence were investigated and analyzed among the students from year’s eight to eleven in MISB. One hundred and eighty three students participated in this study in the first semester of the 2014-2015 academic year. The quantitative data collected by means of the EMI questionnaire, the findings indicated that the participants had average levels of both emotional intelligence and musical intelligence and there were no significant differences in the emotional intelligence of the participants according to year levels and gender. There was no significant difference in the musical intelligence of the participants according to year levels. However, a significant difference was found in the musical intelligence of the participants according to gender. Furthermore, a positive relationship was found between emotional intelligence and musical intelligence. In addition to the results of this study, recommendations for practice and future research are also provided.